2005
DOI: 10.1056/nejmoa051424
|View full text |Cite
|
Sign up to set email alerts
|

Effector Memory T Cells, Early Metastasis, and Survival in Colorectal Cancer

Abstract: Signs of an immune response within colorectal cancers are associated with the absence of pathological evidence of early metastatic invasion and with prolonged survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

83
1,369
3
25

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,885 publications
(1,480 citation statements)
references
References 29 publications
83
1,369
3
25
Order By: Relevance
“…Additionally, the cytokines and chemokines released by IMCgp100 redirected T cells are strong attractants of a multitude of other immune cells. The density of tumour‐infiltrating lymphocytes has been shown to be predictive of patient survival for a number of different tumours 37, 38, 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cytokines and chemokines released by IMCgp100 redirected T cells are strong attractants of a multitude of other immune cells. The density of tumour‐infiltrating lymphocytes has been shown to be predictive of patient survival for a number of different tumours 37, 38, 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor was detected on sequential sections using the Invitrogen immunodetection kit (mouse anti-EGFR clone 31G7), as indicated by the manufacturer. After staining, slides were analysed with an image-analysis workstation (Spot Browser version 7; Alphelys), as previously described (Pages et al, 2005). Signal intensity of digitised images was determined using the Spot Browser software; grey values (0 ¼ black to 255 ¼ white) ranged between 102 and 142, and a value inferior or equal to 120 was defined as overexpression.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Accumulating evidence suggests that tumor progression is governed not only by genetic changes intrinsic to cancer cells but also by epigenetic and environmental factors [10]. Previous studies have suggested that immune infiltrates in CRC may be of clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer immunoediting is the ability of the immune system to control and shape cancer, and is the result of three phases, eliminationequilibrium-escape, that function either independently or in sequence [12]. While experimental evidence supports the idea that the innate immune system can promote tumor development through inflammation-dependent mechanisms, infiltration of the tumor by lymphocytes of the adaptive immune system may be a favorable prognostic sign [10]. However, the role of the adaptive immune reaction is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%